Kesesuaian Pelaksanaan Visum et Repertum dalam Pelepasan Informasi Medis di RSU X Bandung : Conformity of Visum et Repertum Implementation in the Release of Medical Information at X Bandung Hospital - Destiana, Dina; Sugiarti, Ida (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2025)
Visum et Repertum is a written statement by a physician concerning a medical examination of a person, whether alive or dead, or a human body, given at the official request of the investigator, in the form of a conclusion and interpretation, made under an oath in the interests of justice. Visum et Repertum has an important role to play in assisting the judge in deciding a case. The aim of this study is to find out the compatibility of the implementation of Visum et Repertum in the release of medical information at X Hospital. The research uses the mixed method that combines quantitative methods with descriptive design and qualitative method with the design of case studies. The sample of this study is a form of Visum et Repertum of 374 forms with sampling of the total sample and the subject is two medical records officers. Data collection using observation sheets and interview guidelines. The results of the research showed the suitability of the implementation of the production of the Visum et Repertum is 85,04%. There are some problems faced by the officers in the execution of the manufacture of the visa et repertum. Officers are expected to be able to correct the implementation of inappropriate procedures so that their services can be performed to the maximum.